Indigenous Constitutionalism and Dispute Resolution Outside the Courts: An Invitation - Drake, Karen (Osgoode Digital Commons, 2020)
The Supreme Court of Canada's jurisprudence on constitutionally protected Aboriginal rights filters Indigenous laws through the lens of liberal constitutionalism, resulting in distortions of Indigenous law. To overcome this constitutional capture, this article advocates for an institution that facilitates dispute resolution between Canadian governments and Indigenous peoples grounded in Indigenous constitutionalism. To avoid a pan-Indigenous approach, this article focuses on Anishinaabe constitutionalism as one example of Indigenous constitutionalism. It highlights points of contrast between Anishinaabe constitutionalism's and liberalism's foundational norms and dispute resolution procedures. This article argues that a hybrid institution—combining features of both liberalism and Indigenous constitutionalism—would merely reproduce the constitutional capture of Aboriginal rights jurisprudence. It also illustrates how the procedures of talking circles—which are one means of giving effect to persuasive compliance—promote the voice of all involved. Finally, this paper argues that from the perspective of Anishinaabe constitutionalism, the non-binding nature of the processes offered by the new institution would be a strength, not a drawback.